Management of perio-endo interface complex case with NaOCl photoactivated with 980 nm to optimize root canal system decontamination with 12-month follow-up - Reem Hanna; Ioana Cristina Miron; Stefano Benedicenti (Folia Medica)
Root canal system decontamination is recognized as one of the main pillars of successful endodontic treatment, although variations in the efficacy of current disinfection methods have been reported. In light of this, the present study investigated the activation of 5.25% sodium hypochlorite (NaOCl) using a 980 nm diode laser (laser-activated irrigation) as an adjunct to conventional decontamination, with the addition of photobiomodulation therapy. The objectives were to achieve optimal clinical outcomes over long-term follow-up, to alleviate post-endodontic pain, and to propose effective decontamination treatment protocols. A 57-year-old female patient presented with a perio-endo lesion of the lower second premolar teeth, which was associated with Grade III mobility. The treatment strategies included conventional decontamination, laser-activated irrigation, and photobiomodulation. Periodontal parameters, tooth mobility, and periapical healing were assessed at baseline and then at 3, 6, and 12 months. The results showed a significant improvement in these clinical variables, as well as a reduction in post-endodontic pain following photobiomodulation irradiation. The combination of 980 nm laser-activated irrigation and conventional decontamination was found to be significant in optimizing treatment outcomes. However, the study concludes that extensive comparative studies with larger datasets are needed to further validate these results.